Biomarkers associated with lower limb muscle function in individuals with sarcopenia: a systematic review. Issue 6 (17th August 2022) - Jones, Rebecca Louise; Paul, Lorna; Steultjens, Martijn P.M.; Smith, Stephanie Louise
Abstract: Lower limb muscle dysfunction is a key driver for impaired physical capacity and frailty status, both characteristics of sarcopenia. Sarcopenia is the key pathway between frailty and disability. Identifying biological markers for early diagnosis, treatment, and prevention may be key to early intervention and prevention of disability particularly mobility issues. To identify biological markers associated with lower limb muscle (dys)function in adults with sarcopenia, a systematic literature search was conducted in AMED, CINAHL, Cochrane Library, EMBASE, Medline, PubMed, Scopus, SPORTDiscus, and Web of Science databases from inception to 17 November 2021. Title, abstract, and full‐text screening, data extraction, and methodological quality assessment were performed by two reviewers independently and verified by a third reviewer. Depending on available data, associations are reported as either Pearson's correlations, regression R 2 or partial R 2, P value, and sample size (n). Twenty eligible studies including 3306 participants were included (females: 79%, males: 15%, unreported: 6%; mean age ranged from 53 to 92 years) with 36% in a distinct sarcopenic subgroup (females: 73%, males: 19%, unreported: 8%; mean age range 55–92 years). A total of 119 biomarkers were reported, categorized into: genetic and microRNAs ( n  = 64), oxidative stress ( n  = 10), energy metabolism ( n  = 18), inflammation ( n  = 7), enzyme ( n  = 4), hormone ( n  = 7), bone ( n  = 3), vitamin ( n  = 2), and cytokine (n  = 4) markers) and seven lower limb muscle measures predominately focused on strength. Seven studies reported associations between lower limb muscle measures including (e.g. power, force, and torque) and biomarkers. In individuals with sarcopenia, muscle strength was positively associated with free testosterone ( r  = 0.40, P  = 0.01; n  = 46). In analysis with combined sarcopenic and non‐sarcopenic individuals, muscle strength was positively associated with combined genetic and methylation score (partial R 2  = 0.122, P  = 0.03; n  = 48) and negatively associated with sarcopenia‐driven methylation score (partial R 2  = 0.401, P  < 0.01; n  = 48). Biomarkers related to genetics ( R 2  = 0.001–0.014, partial R 2  = 0.013–0.122, P  > 0.05; n  = 48), oxidative stress ( r  = 0.061, P  > 0.05; n  ≥ 77), hormone ( r  = 0.01, ρ = 0.052 p  > 0.05, n  ≥ 46) and combined protein, oxidative stress, muscle performance, and hormones ( R 2  = 22.0, P  > 0.05; n  ≥ 82) did not report significant associations with lower limb muscle strength. Several biomarkers demonstrated associations with lower limb muscle dysfunction. The current literature remains difficult to draw clear conclusions on the relationship between biomarkers and lower limb muscle dysfunction in adults with sarcopenia. Heterogeneity of biomarkers and lower limb muscle function precluded direct comparison. Use of international classification of sarcopenia and a set of core standardized outcome measures should be adopted to aid future investigation and recommendations to be made.